LEGAL REGULATION OF LABOR MIGRATION IN THE 1930s - O. V. Il'ina (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки, 2020)
Background. The relevance of the study is determined by the need to identify various migration flows of rural population, including those carried out under the control of the state, and their impact on demographic processes in rural society. The aim of the study is to characterize the organized set as a form of movement of peasants from the village to the city. Materials and methods. The results of the study are based on the analysis of normative and legal sources that regulated the preparation and conduct of an organizational set among peasants, as well as statistical materials characterizing quantitative and qualitative indicators of the dynamics of the rural population. The methodology of the study is based on historic-comparative and statistical methods, the use of which allowed to identify the causes, content and results of state policy in the field of personnel formation of industrial enterprises in the period of industrialization. Results. The main forms of migration of rural residents are studied, the place and importance of organizational sets in the implementation of economic tasks of the state is determined, the dynamics in the regulation of the movement of peasants from natural forms to the migration policy organized by the state is shown. Conclusions. On the basis of the analysis of documentary and historiographical sources, the conclusion is made about the contradictory nature of the state’s measures to form a cadre of workers among the peasants, it is revealed that the organizational sets occupied an insignificant place in the mechanical movement of the rural population and did not have a significant impact on the change in the number of villagers.